49.4k views
1 vote
What is the solution to this system of linear equations?

2x + y = 1

3x – y = –6

2 Answers

4 votes


\left \{ {{2x+y=1} \atop {3x-y=-6}} \right.  \\ 5x=-5\\ x=-1\\ 2(-1)+y=1\\ -2+y=1\\ y=3

User Tomasz Rup
by
5.2k points
0 votes
From the first equation:
y = 1 - 2x

Then you can substitute that into the second equation:
3x - (1 - 2x) = - 6
3x - 1 + 2x = - 6
5x = -5
x = - 1

Since you know x, you can find y using the equation y = 1 - 2x

y = 1 - 2(-1)
y = 1 + 2
y = 3

Therefore x = - 1 and y = 3
User Georgi Gerganov
by
4.8k points